WORKERS’ RIGHT TO A SAFE WORK ENVIRONMENT (CIPEEX, 2025)
This study aims to analyze the right of workers to a safe work environment, as provided for in labor legislation and international treaties. The focus is on understanding employers' obligations and the role of public policies in promoting safe and healthy working conditions, as well as assessing the main challenges faced in implementing these measures. The research was conducted based on a literature review, including national legislation, such as the Consolidation of Labor Laws (CLT), and international conventions from the International Labor Organization (ILO) related to health and safety at work. Case studies from different economic sectors were also analyzed, focusing on risk areas, such as construction, agriculture and chemical industries. In addition, a documentary analysis of labor inspection reports and data on occupational accidents and illnesses was carried out. The results indicate that, despite the existence of clear standards and regulations to ensure a safe working environment, there are still a significant number of workers exposed to dangerous conditions. Among the main factors identified are the lack of adequate supervision, non-compliance with standards by employers and the lack of training programs to raise awareness about safety at work. The study also highlights that the sectors with the highest accident rates are those that involve manual work and operations in dangerous environments. The research showed that, when implemented, measures such as Personal Protective Equipment (PPE), regular training and risk management systems significantly reduce occupational accidents and illnesses. It is concluded that the right to a safe work environment is fundamental to protecting the health and dignity of workers. However, its implementation faces substantial challenges, especially in higher risk sectors and in companies that do not comply with legal obligations. It is essential that there is greater supervision, the application of penalties in cases of negligence and the strengthening of public policies aimed at preventing accidents and promoting occupational health. Continuous awareness among employers and workers, combined with the provision of adequate resources to implement safety measures, is essential to ensure that everyone can work in safe and healthy conditions.
Keywords: labor law; work environment; safe work; employees